The effect of virtual reality applications on treatment outcomes in lower extremity rehabilitation: a systematic review - Hande Tunc; Mehtap Bakar; Selim Ozen; Gokce Leblebici; Devrim Tarakci (Advances in Rehabilitation)
A noticeable trend in rehabilitation is the growing use of virtual rehabilitation(VR) in musculoskeletal-related areas. Yet, despite growing interest, the levels of evidence available are insufficient to warrant its clinical use in orthopedic rehabilitation. This study intends to explore the impact of these applications in the context of orthopedic treatment. The research covers the period from 2010 to 2023, utilizing databases such as PubMed, Web of Science, PEDro, and Cochrane. The study design adheres to the PRISMA protocol, and the quality and risk of bias were assessed by the Revised Cochrane Risk-of-bias Tool for Randomized Trials and PEDro scale from the Physiotherapy Evidence Database. This study encompasses 12 studies, with the selected articles categorized based on balance, muscle strength, and pain. All of the selected studies achieved high methodological quality on the PEDro scale. The findings indicate that both VR-based exercise therapy and conventional therapy show promising results in determined outcomes, but VR applications typically yielded superior or comparable results to conventional treatments for balance and muscle strength. Also, VR applications were found to have roughly equivalent effects on pain as conventional treatments. The use of VR applications might be seen as an alternative to conventional approaches, depending on the primary objectives of the treatment and the specific needs and expectations of the patient.